STUDY OF MICROELEMENT IMBALANCES IN INTESTINAL HELMINTHIASIS AND IMPROVEMENT OF THEIR CORRECTION - Shodmonov Iskandar Sergeyevich (TADQIQOTLAR, 2025)
Intestinal helminthiasis remains a common parasitic disease worldwide and is associated not only with gastrointestinal manifestations but also with systemic metabolic disturbances. Chronic helminth infections can disrupt microelement homeostasis due to impaired intestinal absorption and competition for essential micronutrients.